Aprendizagem cooperativa como estratégia metodológica para desenvolver habilidades investigativas específicas em estudantes universitários - Hernández Huaripaucar, Edgar Martín (2021)
The purpose of the work was to determine the influence of the application of the Cooperative Learning techniques in the development of specific investigative skills in students of Biological Sciences and Chemistry of the National University San Luis Gonzaga, Ica. The sample amounted to 34 students, equally distributed in the experimental group and the control group. The results indicate that the applied techniques positively influenced the development of specific investigative skills. Thus, in the problematization, the control group's achievement in the pretest was 58.82% and in the posttest 61.76%. The experimental group obtained an achievement of 50% and 79.41%, respectively.